Lateral Mass Screws, Pitfalls, and Practis - Abdul Hafid Bajamal (Indoscholar, 2018)
Lateral mass screws represent a unique challenge to practising spine surgeons because this technique is still the most appropriate technique for fixation at the subaxial spine from C3 to C7. There is a wide range of indications for lateral mass screws fixation including acute and chronic instability resulting from tumours, infections, posterior element fractures, posterior ligamentous injuries, post-laminectomy instability, and following multilevel corpectomy and pseudarthrosis after anterior cervical fusion. Lateral mass screws may be inadequate in cases with poor bone quality secondary to fracture, neoplasm, or revision surgery. Pitfalls and practice of this technique will be discussed.